Using Recycled Glass and Zeolite in Concrete Pavement to Mitigate Heat Island and Reduce Thermal Cracks - Erhan Burak Pancar (Advances in Materials Science and Engineering)
Urban heat island (UHI) effect is built environmental issue related to pavements. It is desired to reduce pavement high surface temperature in summer to mitigate UHI effect. High surface temperature also affects slab temperature difference (the top surface temperature minus the bottom surface temperature of the slab). The increased slab temperature difference induces a high possibility of cracking in concrete roads. The prime aim of this study was to reduce the slab surface temperature by using recycled glass as a fine aggregate and zeolite as cement in concrete. Recycled glass was used to replace fine aggregate in proportions of 10%, 20%, and 30% by total weight of aggregate. Zeolite replaced Portland cement in proportions of 10% and 30% for three different proportions of recycled glass concrete mixtures. Optimum proportions were determined by examining mechanical properties of samples and alkali-silica reactions. It was noticed that using recycled glass and zeolite together in concrete reduces pavement surface temperature and temperature gradient in summer.